Validation of deuterium-labeled fatty acids for the measurement of dietary fat oxidation during physical activity - Aarthi Raman; Stephane Blanc; Alexandra Adams; Dale A. Schoeller (Journal of Lipid Research, 2004)
Measurement of 13C-labeled fatty acid oxidation is hindered by the need for acetate correction, measurement of the rate of CO2 production in a controlled environment, and frequent collection of breath samples. The use of deuterium-labeled fatty acids may overcome these limitations. Herein, d31-palmitate was validated against [1-13C]palmitate during exercise. Thirteen subjects with body mass index of 22.9 ± 3 kg/m2 and body fat of 19.6 ± 11% were subjected to 2 or 4 h of exercise at 25% maximum volume oxygen consumption (VO2max). The d31-palmitate and [1-13C] palmitate were given orally in a liquid meal at breakfast. The d3-acetate and [1-13C]acetate were given during another visit for acetate sequestration correction. Recovery of d31-palmitate in urine at 9 h after dose was compared with [1-13C] palmitate recovery in breath. Cumulative recovery of d31-palmitate was 10.6 ± 3% and that of [1-13C]palmitate was 5.6 ± 2%. The d3-acetate and [1-13C]acetate recoveries were 85 ± 4% and 54 ± 4%, respectively. When [1-13C]acetate recovery was used to correct 13C data, the average recovery differences were 0.4 ± 3%. Uncorrected d31-palmitate and acetate-corrected [1-13C]palmitate were well correlated (y = 0.96x + 0; P < 0.0001) when used to measure fatty acid oxidation during exercise.Thus, d31-palmitate can be used in outpatient settings as it eliminates the need for acetate correction and frequent sampling.